2015
DOI: 10.1007/s12020-015-0638-2
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter pollutants and risk of type 2 diabetes: a time for concern?

Abstract: The World Health Organization estimates that worldwide in 2012 around 7 million deaths occurred prematurely due to air pollution, which is now the world's largest single environmental health risk. The higher premature mortality associated with air pollution is due to exposure to small particulate matter of 10 microns (PM10) or less in diameter. Exposure to air pollution has also been suggested as a contributing to diabetes incidence and progression. There are a number of possible biological pathways linking ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 30 publications
4
60
0
1
Order By: Relevance
“…It has been postulated that PM could contribute to diabetes through various pathways including immune activation, the adipose system, hepatic effects and acting on the central nerve system [9,10,11,19,20,21,22]. Nevertheless, there are very few studies testing associations between UFP and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that PM could contribute to diabetes through various pathways including immune activation, the adipose system, hepatic effects and acting on the central nerve system [9,10,11,19,20,21,22]. Nevertheless, there are very few studies testing associations between UFP and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafine particles (UFP), airborne particles with an aerodynamic diameter <0.1 micron [5], could also plausibly affect cardiovascular health due to their small size and large surface area [6]. Nevertheless, despite evidence regarding associations of PM 2.5 with hypertension [7,8] and diabetes [9,10,11], a limited number of studies have investigated the long-term effects of UFP on cardiovascular risks and clinical outcomes. A longitudinal study recently found an association between long-term exposure to neighborhood-scale (1 × 1 km resolution) UFP exposure and inflammatory and coagulation markers [12].…”
Section: Introductionmentioning
confidence: 99%
“…FBG variations in this range are often underappreciated and their potential determinants, especially those not directly related to lifestyle, are understudied. Ambient particulate matter (PM) pollution has recently been suggested as an emerging risk factor for metabolic disorders including impaired glucose regulation (Esposito et al 2016; Rajagopalan and Brook 2012). Cross-sectional and longitudinal studies have revealed that PM is associated with increased risk of diabetes (Andersen et al 2012; Brook et al 2008; Puett et al 2011) and with higher levels of markers of insulin resistance (Kelishadi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most common diseases related to air pollution are those that compromise airways, such as pulmonary deficiency, asthma and changes in lung function [1,2]. Nevertheless, recent studies have reported an association between diabetes and air pollution [3,4].…”
Section: Introductionmentioning
confidence: 99%